The Effect of Student Quotas on Design Education in Interior Architecture Departments - Kalay, Turgut (Journal of Interior Design and Academy, 2024)
Interior architecture education is a comprehensive field that encompasses design, creativity, and various educational subjects such as art, project management, furniture design, and building knowledge. Due to its multidimensional nature, it has become one of the most popular departments in universities. However, the lack of awareness about the scope and limitations of interior architecture education, coupled with students not meeting the required qualifications, has resulted in a significant increase in the student population in these departments. In this study, the impact of this excessive enrollment on the quality of education in interior architecture departments is analyzed. By examining the literature on interior architecture education, it was found that the existing infrastructure, both in terms of technical resources and faculty members, needs to be improved to accommodate the growing student population. The study suggests that a balance should be established between student quotas and the resources available to ensure a high-quality education in interior architecture.